Influence of joint thickness on Type IV cracking behaviour of modified 9Cr-1Mo steel weld joint. (4th May 2019) - Sakthivel, T.; Chandravathi, K. S.; Laha, K.; Mathew, M. D.
ABSTRACT: Effect of joint thickness on Type IV cracking behaviour of modified 9Cr-1Mo steel weld joint has been investigated. Creep tests on multi-pass double-V cross weld joint flat specimens of the steel having thicknesses in the range 1–17 mm have been carried out at 923 K (650°C) and 50 MPa stress. Creep rupture life of the weld joint was found to increase with thickness and reached a maximum value around 10 mm of thickness followed by decrease with further increase in thickness. Failure in the weld joints occurred in the soft intercritical region of the heat-affected zone (HAZ). Creep strain localisation was observed at the fractured location and was more in the thinner weld joints than in the thicker weld joint. Creep cavitation in the intercritical region of HAZ close to the unaffected base metal was more extensive at the mid-location of the weld pass, where the HAZ width was relatively larger and hardness was lowest. The type IV cavitation in intercritical HAZ was more extensive in thicker joint, whereas creep strain concentration in the intercritical HAZ was more in thinner weld joint. Creep cavitation in the joint was more pronounced at near mid-thickness locations than those beneath the specimen surface. Joints of intermediate thickness possessed higher creep rupture life because of relatively less accumulation of creep deformation coupled with lower creep cavitation in the intercritical region of HAZ.